Research in Ump - Putra Mohd Darul Ridzuan, Rosli (Penerbit UMP, 2014)
Research is one of the main contributing factors to the development of a university. It also contributes directly to the progress of nation building especially when it involves the country's policy and economy. The result of a good research can be presented by way of disseminating the knowledge in lecture room, commercialising the product or it becoming a continuation reference for other researchers. It means that every research is a concept. It can also be a rigid process of propagating knowledge in lecture room only.